Being the Change. 12 ways foundations are transforming themselves to transform their impact - and Ridgway, Abigail; Bockstette, Valerie; Seneviratne, Andria; Cain, Miya; Foster, Tracy (FSG, 2018)
Many foundations are adopting new approaches for creating social change—approaches that aim to influence the actions and investments of the public and private sector, as well as address the complex conditions that hold social problems in place.Based on interviews with 114 practitioners representing 50 foundations and 8 philanthropic services organizations, Being the Change explores how foundations are applying their assets, knowledge, skills, networks, and people in new ways in order to create impact at scale and change systems.